Stereotip Gender dan Wacana Maskulinitas dalam Novel Di Tanah Lada Karya Ziggy Zezsyazeoviennazabrizkie - Tania Intan (Yinyang: Jurnal Studi Islam Gender dan Anak, 2021)
This study aims to uncover gender stereotypes and discourses of masculinity that are scattered in the novel Di Tanah Lada by Ziggy Zezsyazeoviennazabriskie. The method used is descriptive-qualitative with a gender study approach. Data in the form of words, phrases, and sentences were collected by using literature study techniques and taking notes. The theoretical basis used comes from Connell, Feasey, Kimmel, and Flood. The results show that the novel is narrated from the girl character, Salva, who is innocent and honest. Despite these relative deviations, the novel Di Tanah Lada adopts traditional gender stereotypes. Almost all male characters are depicted as superior, dominant, and become perpetrators of violence, so that they are associated with evil male characters. On the other hand, female characters are shown as inferior, weak, and dependent. The masculinity discourse that is built supports traditional gender stereotypes which are still considered acceptable in the contemporary context.